Linguistics : an introduction - McGregor, William, 1952- (London ; New York : Continuum, 2009)
Linguistics is a fresh and contemporary introductory textbook for all students of linguistics and language studies. Firmly based around taught courses and catering to student needs, it addresses all the topics that a student will need in their initial and subsequent study of language. With key terms, further reading, questions at the end of each chapter, exercises and key paragraphs in stand-out boxes, this is a firmly pedagogic text that takes difficult concepts and explains them in an easy to understand way, with examples taken from a range of languages across the world. Global in its scope
List of Figures List of Maps List of Tables Preface Acknowledgements Abbreviations and Conventions Used in Examples 1 Introduction Part I: LANGUAGE: SYSTEM AND STRUCTURE 2 Sounds of Language: Phonetics and Phonology 3 Structure of Words: Morphology 4 Lexicon 5 Structure of Sentences: Syntax 6 Meaning Part II: LANGUAGE: A HUMAN PHENOMENON 7 Sociolinguistics: Language in Its Social Context 8 Psycholinguistics: Language, the Mind and the Brain 9 Language Acquisition 10 Language in Its Biological Context Part III: LANGUAGE: UNIFORMITY AND DIVERSITY. 11 Unity and Diversity in Language Structure 12 Language Change 13 Languages of the World Glossary A B References C D E F G H I J K L M N O P R S T U V W Y Z Language Index A B C D E F G H I J K L M N O P Q R S T U V W X Y Z Name Index A B C D E F G H J K L M P R S T W Y Subject Index A B C D E F G H I K L M N O P R S T U V W Z.
Includes bibliographical references (pages [357]-369) and index.
Keywords: Linguistics